A Study on Alginate encapsulated biosorbent from Spent Coffee Ground (SCG) for wastewater treatment - Teo, Chai Ting (2019)
Spent coffee ground (SCG) biochar-alginate beads act as potential adsorbent for methylene blue (MB) removal. Encapsulation method was applied to produce SCG biochar-alginate bead. The adsorption test were examined at 30°C and the effect of carbonization temperature of biochar, size of biochar particles, adsorbent dosage, alginate concentration and agitation speed were investigated. Thus, the objective of this study was to examine the various variables on the preparation of biochar-alginate beads to achieve optimum condition and compare the performance of biochar with or without encapsulated in MB dye removal. The surface morphology and surface area analysis of adsorbents were analyzed and characterized by Scanning Electronic Microscope (SEM) and Brunauer Emmett Teller (BET). The absorbance readings was measured by using UV-Vis Spectrophotometer. In this study, it was shown that high carbonization temperature at 600°C and small particles size of biochar at 63µm indicated the high effectiveness in MB dye removal. The adsorbent dosage increased from 0.5g to 1.5g showed the increasing efficiency in removing dye and concentration alginate at 2wt% indicated better performance than 1 wt% of alginate concentration in MB removal. The high agitation speed at 200 rpm also can improve the better performance in removing the MB dyes. The optimum result in removing MB dyes was biochar-alginate beads at 600°C carbonization temperature, 63µm of biochar particles, 1.5g of adsorbent dosage and 2 wt% of alginate concentration with applying 200 rpm of agitation speed. Thus, it can concluded that the data obtained in this study represent that SCG biochar-alginate beads are appropriate manner to act as inexpensive and non-toxic adsorbent in removing the cationic dyes.